Mandatum incertum w klasycznym prawie rzymskim - Longchamps de Bérier, Franciszek (Prawo Kanoniczne, 1994)
Mandatum incertum occurs when the terms of this consensual contract are left imprecise by the mandator. The article focuses on the essential determination of the object for the validity of the mandate, therefore the main question is whether mandatum incertum was not unknown to the classical jurists, as there is no doubt it was not void in the Byzantine era. The problem was broadly discussed by several authors, i.e., V. Arangino-Ruiz, G. Donatuti, G. Longo, A. Watson and N. Scapini, though no general agreement among modem jurists was achieved. It seems that terms of mandate are not the same as fines mandati. Fines mandati are not only the intrinsic restrictions given by the mandator, but the purpose to be achived as well. Yes, this purpose could be express or implied, then egressio mandati takes place only when the express boundaries are transgressed. The thorough analysis of relevant classical sources in the full context of the institution allows to state that there is no reason to allege that mandatum incertum was considered invalid in the classical period of Roman law. The strong evidence has been shown that classical jurists recognized mandates with terms left to the discretion of the mandatary. However, the mandatary should execute a commission in favour of the mandator’s interesse and this conduct is estimated according to the boni viri arbitratus.